Nilai Sosial dalam Syair Tari Tradisional Aceh - Armia Armia; Cut Zuriana (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2022)
Aceh has interesting traditional arts and culture, one of which is traditional dance. In general, Acehnese traditional dance is performed accompanied by poetry that is full of meaning and full of life values. This study aims to describe the social values contained in traditional Acehnese dance poetry. This study uses an ethical approach that is in line with the social values of the people discussed. The theory used is the theory of Immanuel Kant and John Stuart Mill which discusses social ethics. Data in the form of phrases, clauses, and sentences were collected by reading and note-taking techniques. Next, the data were analyzed using a qualitative descriptive approach. The results of the study show that in Acehnese traditional dance there are social values in the form of caring values, justice values, responsibility values, cooperation values, and mutual help values